Plasmodium manipulates the expression of host long non-coding RNA during red blood cell intracellular infection - Guang Chen; Shuang-chun Liu; Xiao-yan Fan; Yue-lei Jin; Xin Li; Yun-ting Du (Parasites & Vectors, 2022)
Abstract Background Parasites interact with their host through “direct” and/or “indirect” mechanisms. Plasmodium, for example, either mediates direct physical interactions with host factors or triggers the immune system of the host indirectly, leading to changes in infectious outcomes. Long non-coding RNAs (lncRNAs) participate in regulating biological processes, especially host–pathogen interactions. However, research on the role of host lncRNAs during Plasmodium infection is limited. Methods A RNA sequencing method (RNA-seq) was used to confirm the differential expression profiles of lncRNAs in Plasmodium yeolii 17XL (P.y17XL)-infected BALB/c mice. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to elucidate the potential functions of Plasmodium-induced genes. Subsequently, the effect of specific lncRNAs on the modulation of immune-related signaling pathways in malaria was determined by fluorescence-activated cell sorting, western blot and enzyme-linked immunosorbent assay. Results The data showed that in P.y17XL-infected BALB/c mice, Plasmodium upregulated the expression of 132 lncRNAs and downregulated the expression of 159 lncRNAs. Differentially expressed lncRNAs clearly associated with malaria infection were annotated, including four novel dominant lncRNAs: ENMSUSG00000111521.1, XLOC_038009, XLOC_058629 and XLOC_065676. GO and KEGG pathway analyses demonstrated that these four differentially expressed lncRNAs were associated with co-localized/co-expressed protein-coding genes that were totally enriched in malaria and with the transforming growth factor beta (TGF-β) signaling pathway. Using the models of P.y17XL-infected BALB/c mice, data certified that the level of TGF-β production and activation of TGF-β/Smad2/3 signaling pathway were obviously changed in malaria infection. Conclusions These differentially expressed immune-related genes were deemed to have a role in the process of Plasmodium infection in the host via dendritic/T regulatory cells and the TGF-β/Smad2/3 signaling pathway. The results of the present study confirmed that Plasmodium infection-induced lncRNA expression is a novel mechanism used by Plasmodium parasites to modify host immune signaling. These results further enhance current understanding of the interaction between Plasmodium and host cells. Graphical Abstract